Peningkatan Kompetensi Guru dalam Penulisan Artikel dan Publikasi pada Open Journal System (OJS) - Tri Kurniawati; Menik Kurnia Siwi (Jurnal Ecogen, 2019)
Through community service program we do the training, workshop and assistance for economics teachers as the member of MGMP (Musyawarah Guru Mata Pelajaran) in Bukittinggi City, West Sumatera. The aims of this program are (1) to improve the ability of teachers in the writing of scientific articles, (2) the teachers are able to publish their articles in online journals (3) to motivate the teachers who do not yet have the article to conduct the classroom action research. The participants of this training are 26 economics teachers from high school in Bukittinggi. This activity get positive response from the participants but only two participant can finish the article during the training. Therefore, continues improvement is still need to improve teacher abiliy ini writing scientific article. Keyword: teacher competency, article, publication.